The importance of type of question, psychological climate and subject set in interviewing children about pain. - Ross, D M; Ross, S A; Ross, Dorothea M; Ross, Sheila A (PAIN, 1984)
The child's view of pain is a sparse area in the field of pediatric pain, with interviews providing a major investigative tool. A flurry of interview studies has appeared but their contribution in terms of increasing the pool of information is limited by the indiscriminate use of the supplied-response item format. This paper describes the advantages of the generate-response format as well as the importance of psychological climate and subject set. Data obtained from a large-scale interview project (n = 994) on children's views of their ongoing and past pain experiences provide some support for the interview methodology advocated here.